(3TQM OjhGf GdCNWds - (3CHi SYjO GdScQis; (3CHh eGdc ZjGK Hf ZhK HfWGQbI Hf YeQh GdJZdHj, GdGNWd,J (B90 (3g` ? s
(3ChdgG (B:s
(3bGd GdCNcWd hCSeg ZjGJ Hf ZhK hGdCNWd dbHI hSFd LQjQ Yf faSg hYf GdCNWd hGdaQROb CfG eOjfI GdTYQ hGdaQROb HjJg s
(3BNQgG (B:s
(3BPfhG HGdHjf LjQGfge Ke QGMhG Ke eG HGJhG hGdMeO ddg s
(3QhGjI CHj SYjO GdScQi GdeJhai (B275(3g` Yf GHf MHjHs
(3hCjVkG (B" (3GdOjhGf (B" (3JMJ Qbe (B877s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs